Bronchoscopy Diagnostic Procedures in Central and Peripheral Lesions: A Narrative Literature Review - Syaf, Syarlidina; Sri Indah Indriani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Bronchoscopy is a medical procedure that provides tracheobronchial visualization by placing a bronchoscope and is carried out by a competent doctor. Bronchoscopy is the main interventional procedure used in determining the diagnosis and staging of cancer patients and plays a role in interstitial lung disease and infections. The basic principle of bronchoscopy sampling is carried out with a combination of rinsing, brushing, needle aspiration and biopsy. Cryobiopsy has advantages over conventional forceps biopsy and electrocautery because it can produce tissue without artifacts. Navigated bronchoscopy techniques have facilitated peripheral lung tumor biopsies that have better diagnostic yield than conventional transbronchial biopsies. The combination of navigation bronchoscopy with an ultrathin bronchoscope for peripheral lesions is more effective than either modality.